Student workbook for intermediate microeconomics : price theory and applications - Watson, John Keith (Lexington, Mass. : D.C. Heath, 1995)
Exchange and property. Demand and supply. Consumer choice. Individual demand and elasticity. Consumer behavior. The firm and the theory of production...
Keywords: Microeconomics; Microeconomics